2013
DOI: 10.2355/isijinternational.53.250
|View full text |Cite
|
Sign up to set email alerts
|

Further Assessment of the Kissinger Formula in Simulation of Thermal Desorption Spectrum of Hydrogen

Abstract: The Kissinger-type formula, dX/dt=A(1-X)exp(-Ed/RT), which was thought to be applicable only in detrapping-controlled desorption has proved to be applicable also in the case of diffusion-controlled desorption under certain conditions including existence of effective diffusion coefficient or assumption of Oriani's local equilibrium and pre-exposure of hydrogen before temperature ramp. Analysis indicated that the constant A depends on the specimen geometry and the pre-exponential factor of effective diffusion co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…According to existing studies, peak 1, the first deconvolution peak, has a lower peak temperature as shown in Figure 9a,b. Wei et al [13,[28][29][30] considered that the desorption temperature was proportional to the activation energy through mathematical fitting, and the lower the temperature was, the lower the activation energy was. The hydrogen concentrations are, respectively, 0.528 and 0.566 ppm that are very close.…”
Section: Discussionmentioning
confidence: 99%
“…According to existing studies, peak 1, the first deconvolution peak, has a lower peak temperature as shown in Figure 9a,b. Wei et al [13,[28][29][30] considered that the desorption temperature was proportional to the activation energy through mathematical fitting, and the lower the temperature was, the lower the activation energy was. The hydrogen concentrations are, respectively, 0.528 and 0.566 ppm that are very close.…”
Section: Discussionmentioning
confidence: 99%
“…5,6) Except these two extreme cases much less attention has been paid to desoption in which lattice diffusion has a substantial influence and equilibrium of hydrogen is achieved only partially between the lattice and the trap site. This is called mixed-control desorption henceforth.…”
Section: Influence Of Specimen Thickness On Thermal Desorption Spectrmentioning
confidence: 99%
“…11) The C-L plot is also applicable to diffusion-controlled desorption if pre-exposure is carried out for a sufficiently long time, 5,6) whereas, the ln (ϕ/T p ) vs 1/T p plot, another formula of Kissinger-type desorption proposed by Lee and Lee, 12) does not yield a correct value of detrap energy.…”
Section: Mixed-control Desorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Для определения энергии выхода водорода из дефектов этот подход был впервые использован применительно к железу [10], а в недавней работе [11] он был использован и для вольфрама. Ранее в работах [12,13] исследовались границы применимости формулы (6) для определения энергии выхода водорода из железа, однако использовалось допущение о бесконечно большой скорости рекомбинации. Данная работа посвящена изучению границ применимости формулы (6) для определения энергии выхода водорода из дефектов на примере вольфрама с учётом конечной скорости рекомбинации на поверхности металла.…”
Section: Introductionunclassified